Marketing Mix (4Cs) Affecting Decision to be an Online Degree Student: A Qualitative Case Study of an Online Master’s Degree in Thailand - Sutithep Siripipattanakul; Supaprawat Siripipattanakul; Pongsakorn Limna; Pichakoon Auttawechasakoon (Researchparks Publishing, 2022)
This study aims to explain the influence of the marketing mix (4Cs) on the decision to be an online master’s degree student in Thai people. A purposive sampling of Thai six online master’s degree students from three universities was selected for a qualitative study. The data were analysed employing content analysis and the NVIVO software program. The results show that the 4Cs-marketing mix (communication, cost, convenience, and customer or student centre) is related to the decision to be an online master's degree student at a university in Thailand. Online master’s degree students perceived cost as the highest essential factor, followed by convenience, communication, and customer (student) centre. Educators and program directors should consider marketing mix (4Cs) because these factors influence the decision to be an online master’s degree student in this qualitative research. The implication could help all service sectors find the appropriate marketing mix or customer relationship management (4Cs) for their customers because it influences behavioural intention or decisions among consumers.